Association of iris crypts with acute primary angle closure. Issue 10 (7th March 2017) - Koh, Victor; Chua, Jacqueline; Shi, Yuan; Thakku, Sri Gowtham; Lee, Ryan; Nongpiur, Monisha E; Baskaran, Mani; Kumar, Rajesh S; Perera, Shamira; Aung, Tin; Cheng, Ching-Yu
Abstract : Purpose: To determine the relationship between iris surface features and acute primary angle closure (APAC) in eyes with angle closure. Design: Case-control study involving Asian patients diagnosed with previous APAC, primary angle closure suspect (PACS), primary angle closure (PAC) and primary angle closure glaucoma (PACG) at an eye centre in Singapore between August 2012 and January 2015. Methods: Participants underwent ophthalmic examination and digital slit-lamp iris photography. Iris surface features were graded based on crypts, furrows and colour. Fellow eyes of APAC were compared with PACS and PAC/PACG eyes with regard to their iris surface features. Main outcome measure: Occurrence of APAC. Results: A total of 309 patients (71 APAC, 139 PACS, 47 PAC and 52 PACG) were included (mean age: 67.7±7.2 years and 36.6% male). Compared with PACS, higher crypt grade was significantly associated with lower odds of APAC (OR=0.58 for one grade higher in crypt grade; p=0.027, adjusted for age, gender, ethnicity and pupil diameter). The results remained similar when compared with PAC/PACG group (OR=0.58 for one grade higher in crypt grade; p=0.043). We did not observe any significant associations between iris furrows or colour with presence of APAC. Conclusions: Our study comprising Asian eyes with angle closure suggests that the presence of a higher crypt grading may be protective for APAC. As such, assessing iris surface architecture for crypts could be a new measure for risk stratification of developing APAC in eyes with angle closure.